Hubungan Social Support dengan Perilaku Non Suicidal Self-Injury pada Remaja di Jakarta - Lonika, Mikha; Maharani, Grace Hinna; Carolina, Callista Amanda; Priskila, Vania (Universitas Negeri Malang, 2025)
The increasingly widespread trend of Non-Suicidal Self Injury among teenagers makes the role of social support very important, especially among teenagers who are still experiencing many changes both physically, cognitively, and socio-emotionally. Teenagers' emotional problems that cannot be resolved properly can lead teenagers to negative behaviors, one of which is non-suicidal self-injury (NSSI). This research aims to determine the relationship between Social Support and Non-Suicidal self-injury behavior among adolescents in Jakarta. This research used quantitative research methods, where data was collected through questionnaires that were distributed and obtained by as many as 89 people with an age range of around 12-21 years in Jakarta who had ever engaged in self-harming behavior. The sampling technique for this research uses a probability sampling technique with a correlational quantitative research design. Based on the search results via SPSS 20.0, a correlation coefficient value of -0.342 was obtained with a significance of 0.001, meaning that it has an inverse relationship, meaning that the higher the social support variable will be followed by the lower the non-suicidal self-injury variable and vice versa. Therefore, the research results show that there is a relationship between social support and non-suicidal self-injury behavior in adolescents in Jakarta. AbstrakSemakin maraknya trend non-suicidal self-injury membuat peranan social support menjadi sangat penting khususnya di kalangan remaja yang masih mengalami banyak perubahan baik secara fisik, kognitif, dan sosio-emosional. Masalah emosional remaja yang tidak dapat teratasi dengan baik dapat mengarahkan remaja kepada perilaku-perilaku yang negatif salah satunya adalah tindakan non-suicidal self-injury (NSSI). Penelitian ini bertujuan untuk mengetahui hubungan antara Social Support dengan perilaku Non-Suicidal Self Injury remaja di Jakarta. Penelitian ini menggunakan metode riset kuantitatif, dimana data dikumpulkan melalui kuesioner yang disebarkan dan mendapatkan sebanyak 89 orang dengan rentang usia sekitar 12-21 tahun di Jakarta serta pernah melakukan perilaku menyakiti diri. Teknik sampling penelitian ini menggunakan teknik purposive sampling dengan desain penelitian kuantitatif korelasional. Berdasarkan hasil analisis, diperoleh nilai koefisien korelasi sebesar -0,342 dengan signifikansi sebesar 0,001 yaitu bermakna memiliki hubungan yang berlawanan artinya semakin tinggi variabel social support akan diikuti dengan semakin rendahnya variabel non-suicidal self-injury dan sebaliknya. Oleh karena itu, hasil penelitian menunjukkan bahwa terdapat hubungan social support terhadap perilaku non-suicidal self-injury pada remaja di Jakarta.